Non-muslim citizenship in Islamic law: juristic polemics and Malaysian reality - Ishak, Mohd. Shuhaimi (2015)
The status of non-Muslim minorities in a Muslim nation in present day societies is a contested issue in modern Islamic law. Most of Muslim legists advance the view that non-Muslim minorities cannot enjoy equal rights with Muslims as they are dhimmis. Another group arguing for equal rights, however, maintains that today`s Muslim nation states are totally new political structures to which much of the traditional aspects of classical Islamic law including the notion of dimmah does not apply. This study attempts to show that the traditional concept of dhimmi still somewhat defines the position of non-Muslim minorities in the thinking of the legal scholars. Nevertheless, on critical and fundamental issues of rights, non-Muslims in Malaysia enjoy much greater rights which their counterparts in Muslim majority countries never dreamt of during pre-modern times.